Direct synthesis of β-silicon carbide nanowires from graphite only without a catalyst - Al-Ruqeishi, Majid S.; Nor, Roslan Md; Amin, Yusoff Mohd; Al-Azri, Khalifa (Elsevier, 2010)
One-dimensional (1D) β-SiC nanowires were successfully fabricated on bare Si (1 0 0) substrate using simple carbo-thermal evaporation of graphite at 1200 °C. The obtained β-SiC nanowires were aligned with diameters ranged between 40 and 500 nm. The majority of crystal planes were β-SiC (1 1 1) with other less intensity of (2 0 0), (2 2 0) and (3 1 1). The silicon substrate location inside the furnace found to be critical in the formation of the β-SiC nanowires. Also, introducing oxygen gas as an ambient gas instead of argon reduces the growth at locations close to the graphite source.